Interruption of the fragile X syndrome expanded sequence d(CGG)(n) by interspersed d(AGG) trinucleotides diminishes the formation and stability of d(CGG)(n) tetrahelical structures - Weisman-Shomer, Pnina (Oxford University Press, 2000)
Fragile X syndrome is caused by expansion of a d(CGG) trinucleotide repeat sequence in the 5′ untranslated region of the first exon of the FMR1 gene. Repeat expansion is thought to be instigated by formation of d(CGG)(n) secondary structures. Stable FMR1 d(CGG)(n) runs in normal individuals consist of 6–52 d(CGG) repeats that are interrupted every 9–11 triplets by a single d(AGG) trinucleotide. By contrast, individuals having fragile X syndrome premutation or full mutation present >54–200 or >200–2000 monotonous d(CGG) repeats, respectively. Here we show that the presence of interspersed d(AGG) triplets diminished in vitro formation of bimolecular tetrahelical structures of d(CGG)(18) oligomers. Tetraplex structures formed by d(CGG)(n) oligomers containing d(AGG) interspersions had lower thermal stability. In addition, tetraplex structures of d(CGG)(18) oligomers interspersed by d(AGG) triplets were unwound by human Werner syndrome DNA helicase at rates and to an extent that exceeded the unwinding of tetraplex form consisting of monotonous d(CGG)(18). Diminished formation and stability of tetraplex structures of d(AGG)-containing FMR1 d(CGG)(2–50) tracts might restrict their expansion in normal individuals.